Inhibition of activity/expression, or genetic deletion, of ERO1α blunts arsenite geno- and cyto-toxicity. (October 2022) - Guidarelli, Andrea; Spina, Andrea; Fiorani, Mara; Zito, Ester; Cantoni, Orazio
Abstract: Our recent studies suggest that arsenite stimulates the crosstalk between the inositol 1, 4, 5-triphosphate receptor (IP3 R) and the ryanodine receptor (RyR) via a mechanism dependent on endoplasmic reticulum (ER) oxidoreductin1α (ERO1α) up-regulation. Under these conditions, the fraction of Ca 2+ released by the RyR via an ERO1α-dependent mechanism was promptly cleared by the mitochondria and critically mediated O2 −. formation, responsible for the triggering of time-dependent events associated with strand scission of genomic DNA and delayed mitochondrial apoptosis. We herein report that, in differentiated C2C12 cells, this sequence of events can be intercepted by genetic deletion of ERO1α as well as by EN460, an inhibitor of ERO1α activity. Similar results were obtained for the early effects mediated by arsenite in proliferating U937 cells, in which however the long-term studies were hampered by the intrinsic toxicity of the inhibitor. It was then interesting to observe that ISRIB, an inhibitor of p-eIF2 alpha, was in both cell types devoid of intrinsic toxicity and able to suppress ERO1α expression and the resulting downstream effects leading to arsenite geno- and cyto-toxicity. We therefore conclude that pharmacological inhibition of ERO1α activity, or expression, effectively counteracts the deleterious effects induced by the metalloid via a mechanism associated with prevention of mitochondrial O2 −. formation. Graphical abstract: Image 1 Highlights: ISRIB suppresses ERO1α expression induced by arsenite. ISRIB and EN460 prevent the cyto- and geno-toxic responses induced by arsenite. The protective effects of ISRIB or EN460 are mimicked by the ERO1α KO phenotype.